Pelatihan Pembuatan Konten Kreatif sebagai Sarana Promosi pada Pengelola Wisata Pereng Puteh di Kelurahan Bandungan - Karsinah Karsinah; Nadia Indah Femmithasari; Rizky Candra Satria; Mahbub Amrulloh Ikhsan; Galih Pangestu Nugroho (Universitas Negeri Semarang, 2026)
Creating creative content is an effort to increase awareness or attention toward a tourist destination. This training aims to raise awareness among the community, particularly in the Piyoto area, which is known as a tourist village, about the importance of promotion through social media. The method of implementing this activity consists of three stages: preparation, training implementation, and evaluation. This activity involved local youth organizations and tourism managers as training participants. The results of the training indicate that creative content creation using Canva and CapCut is highly beneficial for participants, as it encourages them, especially the youth, to become more active, innovative, and creative. After the training, the youth became more active in creating and sharing creative content featuring Pereng Puteh tourism through social media. Participants also gained an understanding of the basics of video editing and graphic design, making it easier for them to apply these skills. The goal of this activity is to increase the recognition of the tourist village's potential among the wider community and to boost the number of visitors to Pereng Puteh.